Can Regional Spending Management Policies Improve Human Development Index? - Iwa Kartiwa Karpi; Yanne Yuniarti Widayat; Novi Eka Ratnasari; M.D Enjat Munajat (The Journal of Indonesia Sustainable Development Planning, 2022)
The management of expenditure carried out by local governments until now is considered not effective and efficient enough, so the government, through Law Number 1 of 2022 (articles 146 and 147) seeks to increase the effectiveness of regional expenditure in regional development by regulating the proportion of employee spending and public service infrastructure spending. This article aims to evaluate regional spending management policies in increasing Human Development Index (HDI) in the Bima regency. This regency was chosen as the research location because it has a fairly large employee expenditure allocation which is 49.29 percent of the total regional expenditure, with an increase in HDI of 0.36. Data analysis was carried out using Tableau applications and cost-effectiveness analysis. The results show that in comparison to other Indonesian eastern districts, the Bima region does not manage regional expenditures efficiently. Meanwhile, the results of the 2022-2025 HDI forecast only increased by 0.611 per year. The estimated HDI in 2024 is 69,02863, which is still far below the 2024 HDI target of 75.54. Suggestively, the Bima regency needs to allocate budgets selectively for the HDI driving sector and decrease the employee spending rate.